2013
DOI: 10.3329/jueb.v2i0.16329
|View full text |Cite
|
Sign up to set email alerts
|

Environmental and Socio-economic Impacts of Salinity Intrusion in the Coastal Area: A Case Study on Munshigong Union, Shymnagor, Satkhira

Abstract: One of the major problems in the coastal zone of Bangladesh is Salinity intrusion. It is increasing alarmingly due to natural and anthropogenic reasons. salinity. Salinity is causing decline in soil productivity and crop yield which results in severe degradation of bio-environment and ecology. So, a study has and socio-economic condition of the worst salinity affected Munshiganj union of Satkhira district. The study was conducted on the basis of primary and secondary both data sources. To collect pri different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 2 publications
0
12
0
Order By: Relevance
“…One sub-district from each identified district and three unions from each sub-district were selected though a field analysis of these three districts. Study villages were selected purposively based on earlier studies, which indicated vulnerability of all three locations to multiple and frequent disasters [18][19][20][21][22][23][24]. Considering such vulnerability, these study areas were selected to represent flood, cyclone and water logging in order to explore the variations in awareness among inhabitants of different locations.…”
Section: Study Area and Methodologymentioning
confidence: 99%
“…One sub-district from each identified district and three unions from each sub-district were selected though a field analysis of these three districts. Study villages were selected purposively based on earlier studies, which indicated vulnerability of all three locations to multiple and frequent disasters [18][19][20][21][22][23][24]. Considering such vulnerability, these study areas were selected to represent flood, cyclone and water logging in order to explore the variations in awareness among inhabitants of different locations.…”
Section: Study Area and Methodologymentioning
confidence: 99%
“…Salt in soil is one of the most important environmental problems of Bangladesh. Reduction of freshwater flow from upstream causes salinity intrusion and salinization of ground water in Bangladesh [1]. The coastal area covers about 20% of total land and over 30% of the net cultivable area of Bangladesh [2].…”
Section: Introductionmentioning
confidence: 99%
“…The coastal area covers about 20% of total land and over 30% of the net cultivable area of Bangladesh [2]. Salinity affected around 53% of coastal soils of the country [1], however, soil salinity fluctuates with seasons in this area. Rice (Oryza sativa L.) is the main crop in the coastal zone cultivated mainly rain fed during the monsoon when soil salinity is lowered.…”
Section: Introductionmentioning
confidence: 99%
“…Salt-affected soils are identified by excessive levels of water-soluble salts, especially sodium chloride (NaCl) (Tanji, 2002). Salinity is causing decline in soil productivity and crop yield which results in severe degradation of bio-environment and ecology (Hoque, Saika, Sarder, & Biswas, 2013) as well as responsible for low cropping intensity in coastal area (Rahman & Ahsan, 2001).…”
Section: Introductionmentioning
confidence: 99%